Efficacy of Topical Andrographis Paniculata Extract for Pruritus in Chronic Liver Disease: A Randomized, Placebo-Controlled Trial - Chotipong Siripipattanamongkol; Vich Thampanya; Piyaporn Sirijanchune; Nonlawan Chueamuangphan; Watcharee Khunkitti (Siriraj Medical Journal)
Objective: Assessing the effectiveness of topical extract from Andrographis paniculata, which has anti-inflammatory properties, in reducing pruritus in individuals with chronic liver disease.